The prevalence of pediatric asthma in the Islamic Republic of Iran: A review and meta-analysis - javad ghaffari; Mohsen Aarabi (Mazandaran University of Medical Sciences, 2013)
ABSTRACT The prevalence of asthma is inconsistent in different countries and even in regions of a country. Awareness of this prevalence has favorable impacts on health care system planning. The aim of this literature review and meta-analysis was to estimate the prevalence of pediatric asthma in the Islamic Republic of Iran during two recent decades. A search was done in national (SID, Magiran, Irandoc, Iranmedex) and international databases (PubMed and Google Scholar) to find articles which evaluated asthma prevalence in pediatrics and adolescences, using the international study of asthma and allergies in children written questionnaire. Twenty eight articles between 1992 and 2012 with a total of 96822 participants were found. 'Asthma ever' prevalence was 2.7% (95% CI: 1.9 to 3.6) and 3.5% (95% CI: 2.6 to 4.6) in children aged 6-7 and 13-14 years, respectively. 'Wheezing in the past 12 months' were 7.6% (5.6 to 9.8) and 10.7% (95%CI: 8.9 to 12.7) in children aged 6-7 and 13-14 years, respectively. The prevalence of asthma had an increasing trend during the last two decades, therefore, the health care system should be alarmed for more meticulous planning and evaluation to control and prevent asthma.